Validating the effectiveness indicators of social marketing communication campaigns for reducing health-risk behaviors among youth in Thailand - Nottakrit Vantamay, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study aims to validate the effectiveness indicators of social marketing communication campaigns for reducing health-risk behaviors among Thai youth by using a quantitative research with 1,000 undergraduate students aged 18-24 years old in Thailand. A second-order confirmatory factor analysis was used to check compliance with empirical data at the .05 significance level. The findings showed that the effectiveness indicators of social marketing communication campaigns for reducing health-risk behaviors among Thai youth consist of forty-nine indicators from eight core components: 1) attitude toward health-risk behaviors reduction, 2) subjective norms, 3) perceived behavioral control, 4) intention to reduce health-risk behaviors, 5) practices for reducing health-risk behaviors, 6) knowledge in dangers and impacts of health-risk behaviors, 7) campaign brand equity, and 8) communication networks. These new developed effectiveness indicators should be taken into evaluating the effectiveness of social marketing communication campaigns for reducing health-risk behaviors among youtheffectively and efficiently for a sustained success both in Thailand and in international level.